High-dose maternal folic acid supplementation before conception impairs reversal learning in offspring mice - Henzel, Kristin S. (Sci Rep, 2017)
Maternal folic acid (FA) supplementation prior to and during gestation is recommended for the prevention of neural tube closure defects in the developing embryo. Prior studies, however, suggested that excessive FA supplementation during gestation can be associated with toxic effects on the developing organism. Here, we address whether maternal dietary folic acid supplementation at 40 mg/kg chow (FD), restricted to a period prior to conception, affects neurobehavioural development in the offspring generation. Detailed behavioural analyses showed reversal learning impairments in the Morris water maze in offspring derived from dams exposed to FD prior to conceiving. Furthermore, offspring of FD dams showed minor and transient gene expression differences relative to controls. Our data suggest that temporary exposure of female germ cells to FD is sufficient to cause impaired cognitive flexibility in the subsequent generation.